Unique Positive Almost Periodic Solution for Discrete Nonlinear Delay Survival Red Blood Cells Model - Xitao Yang; Siping Tang (Abstract and Applied Analysis)
We obtain sufficient conditions which guarantee the global attractivity of solutions for nonlinear delay survival red blood cells model. Then, some criteria are established for the existence, uniqueness and global attractivity of positive almost periodic solutions of the almost periodic system.